Large-scale plasma-metabolome analysis identifies potential biomarkers of psoriasis and its clinical subtypes. Issue 2 (May 2021) - Kishikawa, Toshihiro; Arase, Noriko; Tsuji, Shigeyoshi; Maeda, Yuichi; Nii, Takuro; Hirata, Jun; Suzuki, Ken; Yamamoto, Kenichi; Masuda, Tatsuo; Ogawa, Kotaro; Ohshima, Shiro; Inohara, Hidenori; et al.
Highlights: Plasma-metabolome analysis identified potential clinical biomarkers of psoriasis. Aspartate had a central role in the difference between psoriasis and controls. Tyramine and vitamin-related pathway showed decreased levels in PsA than PsC. Mucic acid and saturated fatty acids showed increased levels in PsA than PsC. Tyramine plasma levels correlated to PASI scores only in PsC. Abstract: Background: Psoriasis is an immune-mediated skin disease for which the crosstalk between genetic and environmental factors is responsible. To date, no definitive diagnostic criteria for psoriasis yet, and specific biomarkers are required. Objective: We performed metabolome analysis to identify metabolite biomarkers of psoriasis and its subtypes such as psoriatic arthritis (PsA) and cutaneous psoriasis (PsC). Methods: We constructed metabolomics profiling of 130 plasma samples (42 PsA patients, 50 PsC patients, and 38 healthy controls) using a nontargeted metabolomics approach. Results: Psoriasis-control association tests showed that one metabolite (ethanolamine phosphate) was significantly increased in psoriasis samples than in the controls, whereas three metabolites decreased (false discovery rate [FDR] < 0.05; XA0019, nicotinic acid, and 20α-hydroxyprogesterone). In the association test between PsA and PsC, tyramine significantly increased in PsA than in PsC, whereas mucic acid decreased (FDR < 0.05). Molecular pathway analysis of the PsA–PsC association test identified enrichment of vitamin digestion and absorption pathway in PsC ( P = 1.3 × 10 −4 ). Correlation network analyses elucidated that a subnetwork centered on aspartate was constructed among the psoriasis-associated metabolites; meanwhile, the major subnetwork among metabolites with differences between PsA and PsC was primarily formed from saturated fatty acids. Conclusion: Our large-scale metabolome analysis highlights novel characteristics of plasma metabolites in psoriasis and the differences between PsA and PsC, which could be used as potential biomarkers of psoriasis and its clinical subtypes. These findings contribute to our understanding of psoriasis pathophysiology.